Molecular mechanism of lipopeptide presentation by CD1a. - Zajonc, D; Crispin, MD; Bowden, T; Young, D; Cheng, T; Hu, J; Costello, C; Rudd, P; Dwek, R; Miller, M; Brenner, M; Moody, D; et al. (2005)
CD1a is expressed on Langerhans cells (LCs) and dendritic cells (DCs), where it mediates T cell recognition of glycolipid and lipopeptide antigens that contain either one or two alkyl chains. We demonstrate here that CD1a-restricted T cells can discriminate the peptide component of didehydroxymycobactin lipopeptides. Structure analysis of CD1a cocrystallized with a synthetic mycobactin lipopeptide at 2.8 A resolution further reveals that the single alkyl chain is inserted deep within the A' pocket of the groove, whereas its two peptidic branches protrude along the F' pocket to the outer, alpha-helical surface of CD1a for recognition by the TCR. Remarkably, the cyclized lysine branch of the peptide moiety lies in the shallow F' pocket in a conformation that closely mimics that of the alkyl chain in the CD1a-sulfatide structure. Thus, this structural study illustrates how a single chain lipid can be presented by CD1 and that the peptide moiety of the lipopeptide is recognized by the TCR.